PENGARUH PEMBERIAN EKSTRAK DAUN SAMBILOTO (ANDROGRAPHIS PANICULATA) TERHADAP TITER ANTIBODI AYAM RAS PETELUR - Darmansyah; A. Mujnisa; Wempie Pakiding (Wahana Peternakan, 2023)
This experiment aims to determine the effect of sambiloto (Andrographis paniculata) leaf extract on antibody titers of Avian Influenza (AI) and Newcastle Disease (ND) of starter phase laying hens. This study used 100 Isa Brown strain laying hens. The cages used were 20 box cages of 60x50x50 cm size. The research method used is a completely randomized design (CRD) with 5 treatments (T1: 0%, T2: 0,5%, T3: 1%, T4: 1,5% and T5: 2%) of sambiloto (Andrographis paniculata) leaf extract and each treatment was repeated 4 times. The result of the analysis of variance showed that the treatment of sambiloto (Andrographis paniculata) leaf extract had no significant effect (P>0,05) on AI and ND antibody titers at 3, 4 and 5 weeks of age, but has a significant effect (P<0,05) on AI and ND antibody titers at 6 weeks of age. In conclusion, the administrasion of sambiloto (Andrographis paniculata) leaf extract in drinking water was able to accelerate the formation AI and ND antibody titers and was able to maintain higher antibody compared to the control treatment. The administration of sambiloto (Andrographis paniculata) leaf extract in drinking water was able to form and maintain AI and ND antibody titers. Keywords: antibody titers, avian influenza, laying hens, newcastke disease, sambiloto leaf extract